Giant coronary aneurysm caused by Kawasaki disease: consistency between catheter angiography and electrocardiogram gated dual-source computed tomography angiography - Eun-Ha Hwang; Jung-Ki Ju; Min-Jung Cho; Ji-Won Lee; Hyoung-Doo Lee (Korean Pediatric Society, 2015)
We present the case of a 5-year-old child with coronary complications due to Kawasaki disease; this patient unintentionally underwent both dual-source computed tomography (DSCT) coronary angiography and invasive coronary angiographic examination in 2 months. This case highlights the strong consistency of the results between DSCT coronary angiography and invasive coronary angiography. Compared to conventional invasive coronary angiography, DSCT coronary angiography offered additional advantages such as minimal invasiveness and less radiation exposure.